2015
DOI: 10.1161/strokeaha.115.010566
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hematoma Morphologic Appearance on Noncontrast Computed Tomography Predicts Significant Hematoma Expansion

Abstract: Background and Purpose-Hematoma expansion in intracerebral hemorrhage is associated with higher morbidity and mortality. The computed tomography (CT) angiographic spot sign is highly predictive of expansion, but other morphological features of intracerebral hemorrhage such as fluid levels, density heterogeneity, and margin irregularity may also predict expansion, particularly in centres where CT angiography is not readily available. Methods-Baseline noncontrast CT scans from patients enrolled in the Predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 20 publications
1
72
1
1
Order By: Relevance
“…10 More recently, using the same dichotomized scale, Blacquiere and colleagues found an independent association between margin irregularity and hemorrhage-expansion with a sensitivity of 0.69 [0.59–0.78] and a specificity of 0.46 [0.40–0.53] for significant expansion in a sample of 356 patients. 26 Similarly, in a single center retrospective cohort of 1029 patients, irregular margins were found to be independently associated with hemorrhage-expansion (adjusted OR, 1.72 [95% CI, 1.07–2.76]; p = 0.02) with sensitivity and specificity of 0.66 and 0.56 respectively. 7 Finally, although these studies did not specifically investigate the impact on hemorrhage-expansion, several additional reports showed a strong association between hemorrhage margin irregularity and poor clinical outcome, potentially mediated by hemorrhage-expansion.…”
Section: Ncct Biomarkers Of the Risk Of Hemorrhage-expansionmentioning
confidence: 89%
“…10 More recently, using the same dichotomized scale, Blacquiere and colleagues found an independent association between margin irregularity and hemorrhage-expansion with a sensitivity of 0.69 [0.59–0.78] and a specificity of 0.46 [0.40–0.53] for significant expansion in a sample of 356 patients. 26 Similarly, in a single center retrospective cohort of 1029 patients, irregular margins were found to be independently associated with hemorrhage-expansion (adjusted OR, 1.72 [95% CI, 1.07–2.76]; p = 0.02) with sensitivity and specificity of 0.66 and 0.56 respectively. 7 Finally, although these studies did not specifically investigate the impact on hemorrhage-expansion, several additional reports showed a strong association between hemorrhage margin irregularity and poor clinical outcome, potentially mediated by hemorrhage-expansion.…”
Section: Ncct Biomarkers Of the Risk Of Hemorrhage-expansionmentioning
confidence: 89%
“…While, numerous groups have examined the value of other NCCT markers in predicting hemorrhage expansion, 3,8,9,9,19,20 the data regarding their impact on clinical outcome, remains meager. 13 We found that of these other NCCT markers, only hemorrhage irregularity is independently associated with worse functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, the question of whether the presence of hypodensities marks sites of active bleeding or conversely corresponds to impaired local coagulation processes remains unanswered. 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations